Audiodescrição: um recurso de acessibilidade na televisão digital - Ishikawa, Maria Inês Garcia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
New realities and paradigms have been lived, which influence the daily lives of people. It is know that for the development of society in contemporary times, it is essential the access to information to all citizens, aiming a larger number of people involved in this informational process and enabling social inclusion. We face, however, a society that needs to meet diversity and that requires the glimpse of new ways of social inclusion for people with disabilities. To reflect about inclusion comprises the alert that involves essues of normality and particularities of each person. Thus, we sought to develop studies and research about this subject with a Brazilian reality - Santa Luzia Home and School for the Blind in the city of Bauru (SP), that comprised two methodological steps: selective bibliographical research for a selective construction of the theoretical framework, and the development of a field research, supported by this framework. Such research was conducted by: documentary research (for obtaining information about the undestanding of its environment) and also on-site observation, to narrow the trust and relationships with the individual surveyed in a total of 20 people with visual impairment, selected based on their characteristics of visual impairment and with conditions of understanding the topic and offering answers to the interviews. The results obtained allow us to state that audio description is a feature that serves to promote communication accessibility through verbal description of the visual elements autonomy, stimulating imagination and broadening the understanding of those who cannot make use of vision, ensuring the rights to information, accessibility and inclusion. In this sense, it was concluded that audio description should be used in Digital Television because it enables new possibilities for inclusion and possible alternative accessibility in communication media, transforming the visual elements into verbal...

Vivenciam-se novs realidades e novos paradigmas que influenciam o cotidiano das pessoas. Sabe-se que para o desenvolvimento da sociedade na contemporaneidade é indispensável o acesso à informação a todos os cidadãos, viasando um maior número de pessoas envolvidas neste processo informacional, possibilitando a inclusão social. Depara-se, entretanto, com uma sociedade que precisa atender à diversidade e que requer o vislumbre de novos caminhos de inclusão social para pessoa com deficiência. A reflexão sobre a inclusão compreende o alerta que envolve as questões de normalidade e de particularidades de cada pessoa. Desse modo, buscou-se desenvolver estudos e pesquisa envolvendo esse tema junto a uma realidade brasileira - Lar Escola Santa Luzia para Cegos da Cidade de Bauru (SP) que compreendeu duas etapas metodológicas: pesquisa bibliográfica seletiva para a construção de referencial teórico seletivo e o desenvolvimento de pesquisa de campo, apoiada nesse referencial. Referida pesquisa foi realizada mediante: pesquisa documental (para obtenção de informações referentes à compreensão de sua ambiência) e também observação in loco para estreitamento de confiança e de relações com os sujeitos pesquisados, cujo total correspondeu a 20 pessoas com deficiência visual, selecionados com base em suas características de Deficiência Visual, e que apresentaram condições de compreensão do tema e de oferecimento de respostas para as entrevistas. Os resultados obtidos permitem afirmar que a audiodescrição é um recurso que tem a função de promover a acessibilidade comunicacional por meio da descrição verbal dos elementos visuais, proporcionando autonomia, estimulando a imaginação e ampliando o entendimento daqueles que não podem fazer uso da visão, garantindo o direito à informação, acessibilidade e inclusão. Neste sentido, concluiu-se que a audiodescrição deve ser utilizada na Televisão Digital porque...
Keywords: Televisão digital; Acessibilidade; Audiodescrição; Deficientes visuais; Digital television